A hiss before dying : - Brown, Rita Mae (Bantam Books, 2017)
A Hiss Before Dying is a current contemporary mystery exploring wild animal poaching counterpointed with a historical narrative set in America's post-revolutionary past, featuring the characters readers embraced in Tail Gait and Tall Tail